Use of darbepoetin alfa in the treatment of anaemia of chronic kidney disease: clinical and pharmacoeconomic considerations - Carrera, Fernando (Oxford University Press, 2009)
The introduction of erythropoiesis-stimulating agents (ESAs) into everyday clinical practice has greatly improved the care of patients with chronic kidney disease. ESAs have reduced the need for blood transfusions, improved survival, decreased cardiovascular complications and enhanced patient quality of life. The longer acting ESA, darbepoetin alfa (Aranesp®), which can be administered less frequently than traditional ESAs, provides further benefits to both patients and healthcare professionals relative to the epoetins. Clinical studies have shown that darbepoetin alfa administered once every 2 weeks or once every month allows enhanced convenience and cost savings with no compromise in efficacy, while maintaining patients within target haemoglobin ranges.